Pyrazolones Activate the Proteasome by Gating Mechanisms and Protect Neuronal Cells from β‐Amyloid Toxicity. (17th December 2019) - Santoro, Anna Maria; Lanza, Valeria; Bellia, Francesco; Sbardella, Diego; Tundo, Grazia R.; Cannizzo, Alessandra; Grasso, Giuseppe; Arizzi, Mariaconcetta; Nicoletti, Vincenzo G.; Alcaro, Stefano; Costa, Giosuè; Pietropaolo, Adriana; et al.
Abstract: Proteasome malfunction parallels abnormal amyloid accumulation in Alzheimer's Disease (AD). Here we scrutinize a small library of pyrazolones by assaying their ability to enhance proteasome activity and protect neuronal cells from amyloid toxicity. Tube tests evidenced that aminopyrine and nifenazone behave as 20S proteasome activators. Enzyme assays carried out on an "open gate" mutant (α3ΔN) proteasome demonstrated that aminopyrine activates proteasome through binding the α‐ring surfaces and influencing gating dynamics. Docking studies coupled with STD‐NMR experiments showed that H‐bonds and π‐π stacking interactions between pyrazolones and the enzyme play a key role in bridging α1 to α2 and, alternatively, α5 to α6 subunits of the outer α‐ring. Aminopyrine and nifenazone exhibit neurotrophic properties and protect differentiated human neuroblastoma SH‐SY5Y cells from β‐amyloid (Aβ) toxicity. ESI‐MS studies confirmed that aminopyrine enhances Aβ degradation by proteasome in a dose‐dependent manner. Our results suggest that some pyrazolones and, in particular, aminopyrine are promising compounds for the development of proteasome activators for AD treatment. Abstract : Drugs redirected : Inspired by recent reports showing that some outdated painkillers may rescue proteasome activity in mice and attracted by the possibility to repurpose "old" medicines and thus de‐risk the drug development process, we scrutinized a small library of pyrazolones by assaying their ability to augment proteasome activity and protect neurons from amyloid toxicity.